Design, synthesis, structural characterization, in vitro anticancer activity, and in silico studies of some new hydroxylated and fluorinated-substituted hydrazone derivatives - Reşit Çakmak; Eyüp Başaran; Ömer Erdoğan; Suraj N. Mali; Semiha Köprü; Haya Yasin; Shailesh S. Gurav; Giray Topal (Chemical Physics Impact)
Today, due to improved lifestyles and increased survival, the number of new cancer cases and cancer-related deaths continues to increase. In this study, novel hydroxylated and fluorinated-substituted hydrazone derivatives bearing an aromatic nitro moiety (2a-d and 3a-d) were designed as potential anticancer drug candidates, synthesized for the first time, and evaluated for their anticancer activity against chondrosarcoma (SW1353), a common primary malignant cartilage-forming tumor, neuroblastoma (SH-SY5Y), a type of brain cancer, and healthy (L929) cell lines using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) method for 24 h. The chemical structures of the target molecules were confirmed by FT-IR, 1D NMR (1H- and 13C- NMR, and APT), 2D NMR (COSY, HETCOR, and HMBC), and elemental analysis. Some of the compounds targeted against these cancer cell lines showed activity greater than 200 μM, whereas others (2d and 3a) demonstrated significant cytotoxic activity. Among them, compound 3a (IC50 = 9.45 ± 2.14 μM), a fluorinated-substituted hydrazone derivative, showed significant cytotoxic activity against the human SW1353 cell line compared to cisplatin (IC50 = 11.9 ± 0.95 μM). The anti-migratory properties of compounds 2d and 3a in SW1353 cells, were investigated. In particular, compound 3a exhibited anti-migration behavior in SW1353 cells, with a wound closure rate of 22.25 % compared with control cells. Further, scaffolds 2d and 3a exhibited the best docking with target receptor proteins 2OH4 (−8.3 and −8.4 kcal/mol) and 3QX3 (−12.2 and 11.0 kcal/mol), thereby supporting our bioactivity studies. Compounds 2a, 3a, 3b, and 3c showed high gastrointestinal (GI) absorption, with all except 3a being non-permeable to the blood-brain barrier (BBB). Most compounds, except 3d, are non-substrates of P-glycoprotein (P-gp). In conclusion, the in vitro and in silico results of some of the tested compounds indicate that they could be promising molecular frameworks for further studies.